Interaction among branched polyethylenimine (PEI), sodium dodecyl sulfate (SDS) and metal cations during copper recovery from water using polymer-surfactant aggregates - Chen, M; Hankins, NP (Elsevier, 2020)
The application of polymer–surfactant aggregates (PSAs) to recover heavy metal ions from water is a novel treatment process for aqueous metallic effluents. To better employ this strategy, branched polyethylenimine (PEI), sodium dodecyl sulfate (SDS) and copper ions were selected to investigate their interaction in water and to improve the recyclable PSAs process for metal removal and recovery. Electrostatic association between PEI and SDS caused the formation of PSAs, and the addition of SDS to a partially protonated PEI solution caused a pH increase; however, re-dispersal of PSAs could be achieved via an increase in pH. Precipitation of PSAs depended on pH, SDS/PEI concentration ratio and the total concentration of PEI; the optimal SDS/PEI ratio decreased as pH increased, and a higher concentration of PEI showed a greater potential to precipitate. PEI formed a strong complex with Cu2+, with the most stable complex at a PEI/Cu chelation ratio of 4. Acidification decreased the chelation capacity of PEI to Cu2+, because of the competition from protons for amino groups. Complexation with Cu2+ in turn reduced the proton buffer capacity of PEI in a non-acid solution. The removal of Cu2+ increased by increasing the total PEI concentration, or by increasing pH from 1 to above 4. Ionic strength and hardness had no marked effect on Cu2+ removal using the PSAs process. Following the initial interaction among PEI, SDS and Cu2+, the Cu2+ could then be released from the PSAs by acidification and the reuse of the PSAs material could be achieved by alkalization. Copper removal and recovery were still up to 98 % and 88 % after three reuse cycles of the PSAs process, respectively.